Perancangan Sistem Ppic Guna Mengoptimalkan Proses Produksi Cetak Cover LKS (Lembar Kerja Siswa) Di CV Madyotomo - Thaufik Kurniawan; Febrina Agusti; Ringgo Ismoyo Buwono (Politeknik Kampar, 2024)
Printing is an industry that is constantly evolving and adapting to changing market demands, as well as an increasing focus on sustainability. CV Madyotomo is a company engaged in the printing sector. When excessive incoming orders cause a buildup of print orders of up to 110% of production capacity, this makes employees often have to do overtime. The purpose of this research is to design a PPIC system that is useful for planning and scheduling production so that the entire production process can run smoothly and employees don't have to work overtime too often. PPIC system design can be done using Forecasting with the moving average method and single exponential smoothing. From this research, the results of the forecasting methods used for each level are different. For elementary school level (Elementary School) using the Moving Average method. For junior high school level (junior high school) using the single exponential smoothing method. For SMA level (High School) using the single exponential smoothing method. For MPS (Master Production Schedule) production, the number of daily print orders that must be fulfilled is 78,095. The proposed overtime with MPS in 9 days totals 36 hours. The difference in the frequency of company overtime with overtime according to MPS is as much as 28 hours, this of course will also affect the expenses for the wages paid, of course it will be less than before.